2011
DOI: 10.4220/sykepleienn.2011.0061
|View full text |Cite
|
Sign up to set email alerts
|

Store ulikskapar i innhald, utforming og kvalitet på dei generelle skriftelege direktiva

Abstract: P.r.n. medication in nursing homes -varying content, formulation and quality in administration guidelinesBackground: P.r.n. administration guidelines, prepared by the nursing home physician, are used by nursing home staff when the nursing home physician is not present. Concerns are expressed that patient safety can be threatened by varying quality of these guidelines.Objective: To describe the content and the quality of p.r.n. administration guidelines in Bergen municipality.Method: All 33 nursing homes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…nursing home). A possibility is to have medications on stock, as is the case in Norwegian nursing homes [2], an approach which may prevent systems within the systems. It could be general lists of medications allowed to store and administrate when required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nursing home). A possibility is to have medications on stock, as is the case in Norwegian nursing homes [2], an approach which may prevent systems within the systems. It could be general lists of medications allowed to store and administrate when required.…”
Section: Discussionmentioning
confidence: 99%
“…In long-term care institutions, these medications are given based on observations made by healthcare professionals (HCP). «As needed» (as required) medication is also referred to as pro re nata (PRN) [1][2][3]. A cross-sectional study among residents living in residential age care services in Australia, found that the median number of PRN on a medication list was 4 (2-6 interquartile range) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…De fleste studier gjort på dette feltet tar imidlertid for seg pasientenes faste legemidler, legemidler pasienten skal ta til forhåndsbe-stemte tidspunkter. Få studier har sett naermere på forskrivning og reell bruk av legemidler som tas ved behov (også kalt «eventu-eltmedisin») (10)(11)(12)(13) gemidler er oppført på legemiddelkortene kan dessuten vaere fordelaktig, framfor at pasientene får utlevert behovslegemidler fra såkalte generelle skriftlige direktiv (13). Dette er skriftlige tilleggsprosedyrer utarbeidet på hvert sykehjem, for generell ordinasjon av enkelte legemidler når legen ikke er til stede (14).…”
Section: Bakgrunnunclassified